A Model for Enhancing Protein Food Supply Chain Efficiency Through Cold Chain Management in Jakarta - Rendy Riyanto; sri wahyuni (Jurnal Penelitian, 2026)
Food security, particularly concerning protein supply, is a strategic issue facing complex challenges in metropolitan cities like Jakarta. The protein supply chain is highly vulnerable to operational disruptions and climate fluctuations, which trigger price instability and product spoilage. This study identifies the gap between existing cold storage practices and the technology-based best practices needed to address these issues, especially in the context of implementing medium-scale industry solutions that can be adapted for Small and Medium-sized Enterprises (SMEs). Objectives: This study aims to analyze the current state of cold storage management, identify technology-based and non-technical best practices, and develop a model that integrates efficiency, sustainability, and risk management. The ultimate goal is to provide a guideline that can improve the operational performance, quality, and safety of the protein supply chain. Methodology: This study employs a mixed-methods approach with a case study design. Five years of historical data were used for quantitative analysis, supplemented by qualitative data from in-depth interviews with 11 warehouse staff and managers. An assessment of various operational aspects was conducted using a 1-10 scoring system to measure the impact of the transformation from previous to current conditions. Findings: The results of this study show a significant increase in the scores across all aspects of warehouse performance (from an average of 2.125 to 9.125), proving the success of the transformation. These improvements include the normalization of occupancy, enhanced goods flow, traceability, and temperature stability, which directly reduced food loss and operational risks. This transformation also had a positive impact on occupational health and safety (OHS) and organizational culture, which supported productivity and team morale. Practical Implications: This study offers a relevant and applicable best-practice model for SMEs in developing countries to enhance operational efficiency and sustainability. These findings provide valuable insights for managers and policymakers in Jakarta on the importance of strategic investment in cold chain transformation to support food security.